Interventions to optimise transitional care coordination for older people living with dementia and concomitant multimorbidity and their caregivers: A systematic review. Issue 5 (1st November 2020) - Parker, Kirsten J.; Hickman, Louise D.; Phillips, Jane L.; Ferguson, Caleb
Abstract : Background : People living with dementia and multimorbidity are frequent uses of health, amplifying risk of fragmented care when moving between care settings. Objectives : This Systematic review aims to identify interventions to support transitional care for older people living with dementia and multimorbidity, and their caregivers. Methods : A systematic search from January 2000-2018 of academic databases for studies which implemented a transitional care intervention for older people living with dementia and multimorbidity, and their caregivers. Results : Out of 6053 identified citations, 11 studies and 13 papers were included. These studies included 1861 people living with dementia, mean age 80 years and 1503 caregivers, mean age of 69 years. Narrative synthesis identifed six elements of care that optimise outcomes; unmet needs; depression; education and support; physical decline; poor quality of life and; access and knowledge of community services. Conclusion : This review demonstrates the paucity of interventions available to reduce impact and experiences of transitions for this vulnerable population. The need is increasing for further research and development in transitional care.